Dropping out and in: Returning to high school in rural Canada - George, Anne L (University of Ottawa (Canada), 2007)
This qualitative study explored the personal and educational experiences of five adult education students who returned to high school in rural Ontario. Examining the voices of the rural adult education students led to a greater understanding of the meaning of dropping out and returning to high school. A framework for the participants' journey is presented using a lifecourse trajectory perspective. The findings and implications of this study suggest that rural adult students face unique challenges, and that a dialogue around existing policy and practices might strengthen the program even further.
Keywords: Education, Adult and Continuing.; Education, Secondary.